2013
DOI: 10.1186/1471-2229-13-135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Translationally Controlled Tumour Protein (TCTP) on programmed cell death in plants

Abstract: BackgroundTranslationally controlled tumour protein (TCTP), a well known protein of the animal kingdom, was shown to be a Ca2+-binding protein with important functions in many different cellular processes (e.g. protection against stress and apoptosis, cell growth, cell cycle progression, and microtubule organization). However, only little is known about TCTP in plants. Transcript and protein levels of plant TCTPs were shown to be altered by various stress conditions (e.g. cold, salt, draught, aluminium, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 41 publications
3
39
0
2
Order By: Relevance
“…TCTP overexpression also promoted biomass production and it protected plants against salt and osmotic stress. These observations are also consistent with an earlier study that demonstrated the ability of Arabidopsis thaliana TCTP to protect tobacco leafs against induction of programmed cell death (Hoepflinger et al 2013). …”
Section: Note Added In Proofsupporting
confidence: 93%
“…TCTP overexpression also promoted biomass production and it protected plants against salt and osmotic stress. These observations are also consistent with an earlier study that demonstrated the ability of Arabidopsis thaliana TCTP to protect tobacco leafs against induction of programmed cell death (Hoepflinger et al 2013). …”
Section: Note Added In Proofsupporting
confidence: 93%
“…Many studies carried out showed that TCTP took part in various cellular processes (e.g. cell growth, cell cycle progression, microtubule organization, and protection against apoptosis) (Hoepflinger et al 2013). So we designed a series of experiments to demonstrate our assumption.…”
Section: Discussionmentioning
confidence: 94%
“…TCTP is related to interact with a large number of different proteins, however, its binding partners are not well conserved in eukaryotes, and therefore its alternative functions may differ from an organism to another (Wu et al, 2015). It was first identified in mice (Yenofsky et al, 1982) and humans (Gross et al, 1989), and then in other organisms such as yeasts, invertebrates and plants (Bonnet et al, 2000;Gnanasekar et al, 2002;Rao et al, 2002;Hoepflinger et al, 2013). TCTP has been identified in the secretions of animal-parasitic nematodes , and of Meloidogyne enterolobii, a plant parasitic nematode (Zhuo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%